Selection of CO2 utilization options in carbon capture, utilization & storage (CCUS) systems using analytic hierarchy process-data envelopment analysis (AHP-DEA) approach - Tapia, John Frederick (Animo Repository, 2017)
Carbon capture, utilization and storage (CCUS) is one of the most important technologies for reducing greenhouse gas emissions into the atmosphere. Carbon Dioxide (CO2) utilization enables the use of CO2 emissions as input for processes to gain additional revenue. Options for CO2 utilization include CO2 -enhanced oil recovery (CO2 - EOR) and CO2 -enhanced coal methane (CO2 - ECBM) recovery. These techniques involve injection of CO2 into a geological reservoir enabling the increased recovery of oil (CO2 - EOR) and gas (CO2 - ECBM and CO2 - EGR) and storing CO2 emissions into the ground (geological sequestration) simultaneously. Integrating these CO2 utilization operations into a large-scale CCUS system requires selection of oil and gas reservoirs to develop an efficient CCUS infrastructure. In this study, a site screening framework based on the analytic hierarchy process (AHP) and data envelopment analysis (DEA) approaches is developed to select reservoirs for CO2 utilization operations. AHP-based approach is used to aggregate evaluation of qualitative data (reservoir's structural integrity and injection well security) to be integrated into DEA approach in determining site efficiencies. A case study is presented to illustrate the framework. Copyright © 2017, AIDIC Servizi S.r.l..